Investigation of the active components and mechanism of Sanao Decoction in treating chronic cough by network pharmacology and molecular docking - Sheng Mengke; Liu Xing; Liao Yuyao; Li Zhixun; Lyu Lijing; Yang Jiaqi; Shi Xinyuan (KeAi Communications Co., Ltd., 2021)
Objective: To investigate the active components and mechanism of Sanao Decoction (三拗汤, SAD) in treating chronic cough based on network pharmacology and molecular docking. Methods: Active components and their targets were obtained from the Traditional Chinese Medicine Systems and Pharmacology Database and Analysis Platform (TCMSP), Bioinformatics Analysis Tool for Molecular mechANism of Traditional Chinese Medicine (BATMAN-TCM) database, and the literature. The component-target regulatory network and protein-protein interaction (PPI) network were constructed by Cytoscape 3.7.2, and a bioinformatics analysis was performed to identify the significant pathways and their relevant targets. Molecular docking of the core active components and relevant targets was performed. Results: A total of 98 active components of SAD and the corresponding 113 drug targets were identified. The component-target regulatory network and PPI network were successfully established. Results of the bioinformatics analysis indicated that 2 281 Gene Ontology (GO) terms were enriched in chronic cough, including 2 062 terms were in biological processes, 77 in cellular components, and 142 in molecular functions, and top 20 significant pathways in Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Molecular docking study demonstrated that quercetin, luteolin, kaempferol, and naringenin were in good agreement with the corresponding targets. Conclusion: The active compounds of SAD, such as quercetin, luteolin, kaempferol, and naringenin, may act on AKT1, MAPK1, RELA, EGFR, and Bcl-2 and regulate the PI3K-Akt signaling pathway, AGE-RAGE signaling pathway, and fluid shear stress and atherosclerosis pathway to exert the effects of anti-inflammatory, anti-airway remodeling, anti-oxidant stress effects, and repair airway damage, thus treating chronic cough.